Sediment delivery to sustain the Ganges-Brahmaputra delta under climate change and anthropogenic impacts - Jessica L. Raff; Steven L. Goodbred; Jennifer L. Pickering; Ryan S. Sincavage; John C. Ayers; Md. Saddam Hossain; Carol A. Wilson; Chris Paola; Michael S. Steckler; Dhiman R. Mondal; Jean-Louis Grimaud; Celine Jo Grall; et al. (Nature Communications, 2023)
Abstract The principal nature-based solution for offsetting relative sea-level rise in the Ganges-Brahmaputra delta is the unabated delivery, dispersal, and deposition of the rivers’ ~1 billion-tonne annual sediment load. Recent hydrological transport modeling suggests that strengthening monsoon precipitation in the 21st century could increase this sediment delivery 34-60%; yet other studies demonstrate that sediment could decline 15-80% if planned dams and river diversions are fully implemented. We validate these modeled ranges by developing a comprehensive field-based sediment budget that quantifies the supply of Ganges-Brahmaputra river sediment under varying Holocene climate conditions. Our data reveal natural responses in sediment supply comparable to previously modeled results and suggest that increased sediment delivery may be capable of offsetting accelerated sea-level rise. This prospect for a naturally sustained Ganges-Brahmaputra delta presents possibilities beyond the dystopian future often posed for this system, but the implementation of currently proposed dams and diversions would preclude such opportunities.